2021
DOI: 10.1002/chem.202102815
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Inorganic Coordination Chemistry by Spectroscopy of Isolated Molecules: Methods and Applications

Abstract: A unique feature of the work carried out in the Collaborative Research Center 3MET continues to be its emphasis on innovative, advanced experimental methods which hyphenate mass-selection with further analytical tools such as laser spectroscopy for the study of isolated molecular ions. This allows to probe the intrinsic properties of the species of interest free of perturbing solvent or matrix effects. This review explains these methods and uses examples from past and ongoing 3MET studies of specific classes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 146 publications
(188 reference statements)
0
15
0
Order By: Relevance
“…In comparison, free TEMPO has an N−O stretching frequency of ∼1333 cm −1 (the harmonic frequency scaled by 0.97). The complexes [Cu(pyridine)(TEMPO)] + and [(bipy)Cu(TEMPO)] + are doublets and can thus mimic the possible equilibrium between copper(I)‐TEMPO and copper(II)‐temponium [29] . The electron distribution in the complexes suggests that the TEMPO ligand retains the unpaired electron in the π‐bonding orbital of the N−O bond (see the unpaired electron localization at the N−O bond in red in Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, free TEMPO has an N−O stretching frequency of ∼1333 cm −1 (the harmonic frequency scaled by 0.97). The complexes [Cu(pyridine)(TEMPO)] + and [(bipy)Cu(TEMPO)] + are doublets and can thus mimic the possible equilibrium between copper(I)‐TEMPO and copper(II)‐temponium [29] . The electron distribution in the complexes suggests that the TEMPO ligand retains the unpaired electron in the π‐bonding orbital of the N−O bond (see the unpaired electron localization at the N−O bond in red in Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Mass spectrometry can be used to isolate such complexes in the gas phase and study their structure and reactivity properties [20] . The molecular and electronic structure of mass‐selected ions can be studied in detail by photodissociation spectroscopy [24–29] . Spectroscopy in the infrared range provides vibrational spectra.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] In a recent report, cation-π complexes of Ag + with benzene, toluene and furan have been studied with ultraviolet laser photodissociation and photofragment imaging, providing new information on the cation-π bond energies. [31] IR ion spectroscopy has proven to be a valuable tool to shed light on the structural features of complexes of the noble metals silver, [17,[32][33][34][35][36][37][38][39][40] gold [41][42][43][44][45][46] and platinum, [47][48][49][50][51][52][53] with a variety of ligands yielding a wealth of valuable information such that only partial reference may be given here. It has been reported that complexation of Ag + with polycyclic aromatic hydrocarbons is accompanied by substantial charge transfer, emerging from the analysis of the IR bands of the complexes compared to those of the bare ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The current special issue of Chemistry -a European Journal issue comprises 23 contributions in total, 17 of which stem from work that was conducted within the framework of the 3MET.de center, [1][2][3][4]6,[8][9][10][11]14,[16][17][18][19][20][21]23] and six from outside. [5,7,12,13,15,22] There are two reviews: one is focused on elucidating the magnetic benefits and challenges of cooperativity within 3d-4f based coordination clusters of archetypical butterfly type, [21] and the other one highlights more generally the advancement of inorganic coordination chemistry by spectroscopy of isolated molecules in view of the applied methods and the achieved applications.…”
mentioning
confidence: 99%
“…[5,7,12,13,15,22] There are two reviews: one is focused on elucidating the magnetic benefits and challenges of cooperativity within 3d-4f based coordination clusters of archetypical butterfly type, [21] and the other one highlights more generally the advancement of inorganic coordination chemistry by spectroscopy of isolated molecules in view of the applied methods and the achieved applications. [18] Three communications, [3,12,22] one concept article [8] and 17 full papers [1,2,[4][5][6][7][9][10][11][13][14][15][16][17]19,20,23] document and discuss particular 3MET species and their relevance for our understanding of the TM interactions within. A contribution on the development and application of a complete active space spin-orbit configuration interaction program designed for molecule magnets deserves special mention: this manuscript appears in a more specialized sister journal.…”
mentioning
confidence: 99%